2018
DOI: 10.1007/s11695-018-3261-5
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Preoperative Program Non-Completion in Adolescents Referred for Bariatric Surgery

Abstract: These findings indicate that demographic variables, rather than psychological or family factors, were associated with the progression to or withdrawal from surgery. Further assessment is needed to determine specific reasons for completing or withdrawing from treatment, particularly for males and older adolescents, to improve clinical care and reduce attrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The patient attrition rate in our center before and during the COVID-19 pandemic was 8.9% and 25.2%, respectively (an overall attrition rate of 12.7%). Previous studies reported much higher attrition rates, between 22 and 60% [ 2 , 9 , 11 , 12 ]. One of the reasons for this low attrition rate is the full payment of medical expenses by the universal healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…The patient attrition rate in our center before and during the COVID-19 pandemic was 8.9% and 25.2%, respectively (an overall attrition rate of 12.7%). Previous studies reported much higher attrition rates, between 22 and 60% [ 2 , 9 , 11 , 12 ]. One of the reasons for this low attrition rate is the full payment of medical expenses by the universal healthcare system.…”
Section: Discussionmentioning
confidence: 99%